2021
DOI: 10.1182/blood.2020010165
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of concurrent gene mutations in intensively treated patients withIDH-mutated AML: an ALFA study

Abstract: IDH inhibitors are effective in AML, and trials evaluating frontline combinations with intensive chemotherapy (IC) are ongoing. Data on the prognostic significance of co-occurring genetic alterations and allogeneic hematopoietic stem cell transplantation (HSCT) are conflicting in each IDH-mutated subgroup treated by IC, while this information is important for trial design and results interpretation. We retrospectively analyzed 127 IDH1, 135 IDH2R140 and 57 IDH2R172 newly diagnosed AML patients treated with IC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 56 publications
2
28
0
Order By: Relevance
“…The proportions of different IDH variants were comparable to our study. In line with our study, Duchmann et al 39 reported IDH2-R172 to be associated with fewer co-mutations and to be mutually exclusive with NPM1. In their analysis, co-mutations of NPM1 and IDH2-R140 or IDH1-R132…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The proportions of different IDH variants were comparable to our study. In line with our study, Duchmann et al 39 reported IDH2-R172 to be associated with fewer co-mutations and to be mutually exclusive with NPM1. In their analysis, co-mutations of NPM1 and IDH2-R140 or IDH1-R132…”
Section: Discussionsupporting
confidence: 93%
“…While Duchmann et al 39 refer to the ELN2010 classification 40 for subgroup analysis, we used the more recent ELN2017 classification. 22 16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, gene-gene interactions ('epistasis') are likely to affect the combined output of combinations of driver mutations. Some combinations of mutations may synergize at the molecular level, leading to large gains of fitness and clonal dominance, strong association at the population level, and poorer prognosis, as exemplified in AML by the combination of IDH2 and DNMT3A mutations [25,63,126,127]. During AML progression, fitness gains of mutations tend to be lower, owing to partially overlapping effects (diminishing-returns epistasis [64]), progressive alteration of the cellular signaling networks, and increased immunogenicity [9,128].…”
Section: Clonal Evolution Processesmentioning
confidence: 99%
“…The biomarkers associated with clinical response remain unclear. In examining the prognostic significance of co-mutations in IDH-mutant AML, the NPM1 mutation was associated with improved OS in IDH1-or IDH2R140-mutated AML treated with intensive chemotherapy, suggesting a potential group of patients who would particularly benefit from the addition of targeted therapy [36].…”
Section: Idh1 and Idh2mentioning
confidence: 99%